Cost-effective fabrication of NiCo-LDH Ni inverse opal-like electrodes for high current stable supercapacitors - Hiram Eli Torres Soto; Armando Encinas; Joaquín de la Torre Medina (JPhys Materials)
This study presents a cost-effective fabrication process for synthesizing NiCo-layered double hydroxide (NiCo-LDH) active materials on Ni inverse opal (Ni-IO) porous networks anchored on bakelite PCB substrates without using binders. Electrodeposition at a constant reduction potential was used to grow NiCo-LDH coatings on Ni-IO current collectors to investigate the influence of their thickness on the electrochemical performance of NiCo-LDH $@$ Ni-IO electrodes at current densities as high as 184 A g ^−1 . The highest specific capacitance values between 548 F g ^−1 and 588 F g ^−1 and excellent cycling stability after 5000 galvanostatic charge/discharge cycles at 150 A g ^−1 , were achieved using a 67 nm thick LDH coating. Specifically, the capacitance retention of 92% and coulombic efficiency of 99% after the cycle life tests at high current densities validate the remarkable stability of the electrodes. Additionally, remarkable energy and power densities were recorded for electrodes with LDH thickness between 30 and 67 nm, ranging from 49 to 65.7 Wh kg ^−1 and 26.4 to 128 kW kg ^−1 at current densities between 17 and 184 A g ^−1 . The superior cycling stability, high energy and power densities, and cost-effective production of NiCo-LDH $@$ Ni-IO electrodes on commercial PCB phenolic substrates highlight their potential for high-performance supercapacitor applications.